2023
DOI: 10.3389/fpsyg.2023.1192555
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions scale for university students: UEF-1

Abstract: IntroductionExecutive functions are a set of mental abilities that allow human beings to consciously regulate their behavior and, in a university setting, will have a significant impact on student success during professional training.ObjectiveTo develop a scale to assess executive functions in a university setting.MethodUsing a sample of 1,373 university students from Chile (663) and Ecuador (710) between 17 and 33 years old (Mage = 20.53, SD = 2.34). A study was carried out to analyze the psychometric propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In this sense, in a university context, EFs have a significant impact on student success and achievement [10]. In this sense, previous evidence has shown that EFs are linked to academic success, indicating the importance of promoting learning and achievement [5,11,12]. However, EFs not only contribute to the academic performance of students but are also related to mental health, physical health, health-related quality of life (HRQoL), and job success [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, in a university context, EFs have a significant impact on student success and achievement [10]. In this sense, previous evidence has shown that EFs are linked to academic success, indicating the importance of promoting learning and achievement [5,11,12]. However, EFs not only contribute to the academic performance of students but are also related to mental health, physical health, health-related quality of life (HRQoL), and job success [2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that EFs are essential for developing adaptive behaviours that involve diverse ways of processing information, different sensory modalities, and executing responses, including aspects related to memory and emotional regulation [3]. Moreover, higher EFs among university students have been associated with various benefits [2,4,5]. Complementary to the above, EFs exhibit varying profiles depending on the developmental stage of humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation